Applying Inclusive Design and Digital Storytelling to Facilitate Cultural Tourism: A Review and Initial Framework - Kittichai Kasemsarn; David Harrison; Farnaz Nickpour (Heritage, 2023)
This article aims to review and identify key challenges and opportunities in the interrelationship between cultural tourism, inclusive design, and digital storytelling fields. The literature review included searching Scopus, ScienceDirect, and Google Scholar for three main field keywords, drawing 421 articles between 1990 and 2022. Content analysis was applied to literature findings and five categories with twenty-three themes emerged accordingly: (1) issues in cultural tourism; (2) diversity in museums; (3) inclusive design in museums; (4) motivation in museums; and (5) digital storytelling in museums. The article further discusses the nuanced relationship between these three fields and proposes an initial framework to help future growth of cultural tourism through increasing visitors’ motivation and diversity. As such, the work aims to facilitate cultural tourism as an activity that better reflects the diversity of its potential audiences and proactively addresses their needs, requirements and interests.
Keywords: Museums and Cultural Heritage; Diverse Aspects of Tourism Research; Digital Storytelling and Education